Design and development of Acrylic Die for producing wax pattern to gabricate hip bone joint - Shaha, Sugrib Kumar; Khan, Ahsan Ali; Haque, Md. Mohafizul (Elsevier, 2011)
In the present study to produce a typical hip joint, Investment casting has been selected as casting method since this process can give optimum properties of the product having complex geometry with biocompatible material. In order to perform this casting, a die or mould is needed to fabricate wax pattern, which will be used to make ceramic investment for the hip joint. Thus, this study includes the modification of design together with fabrication of a typical hip joint casting dies with acrylic. Throughout the project,modulus of casting and riser has been calculated and accommodated with the main hip joint die design. The hip-bone joint design has been generated using CATIA V5 software before it is converted into numerical control (NC) codes to machine the two acrylic slabs of the acrylic dies using Vertical Machining Center (VMC). Thus, the acrylic dies for hip bone joint are now ready for making wax pattern intended to produce ceramic investment for casting the required joint with biocompatible material.